Beyond the puff: qualitative insights into smoking behaviours and societal perceptions among university students in India - Pankaj Chaudhary; Seemadevi Thangeswaran; Naganandini Sampath; Kumar Gaurav Chhabra; Avishek Singh; Shweta Dangi (BMJ Open)
Objectives The objective of the study was to understand the smoking behaviour of adults and how societal perceptions influence the smoking behaviour of university students.Design Qualitative study.Setting National Institute of Medical Sciences university, India.Participants 20 face-to-face interviews were carried out among university students who were in the age group of 19–30 years using a combination of purposive sampling, followed by snowball sampling methods.Results Qualitative responses revealed that stress, cravings for cigarettes and mealtimes were key triggers for smoking behaviour. Many participants felt guilty about their smoking and often became irritated by advice from non-smoking friends. All participants had experienced negative health effects, including physical and sensory issues, as well as other adverse experiences. Students expressed a dislike for judgemental attitudes from society. They respected elders and found it difficult to smoke in front of them. Rather than being blamed for their smoking, they preferred supportive assistance to help them quit.Conclusions The study highlights the importance of understanding college students’ smoking behaviour, as it greatly influences their smoking habits. Cessation efforts should target this group and emphasise the negative experiences associated with smoking. Additionally, students recommend creating a non-judgemental and supportive environment to aid in quitting, rather than a judgemental and blaming society.